"If we don't speak the language, we aren't offered the same opportunities": Qualitative perspectives of palliative care access for women of color living with advanced breast cancer - Nithya Krishnamurthy; Daniel David; J. Nicholas Odom; Krystina Mathelier; Jenny J. Lin; Cardinale Smith; Maria Peralta; Dolores Moorehead; Melissa Mazor (Elsevier, 2024)
Context: Despite efforts to enhance equity, disparities in early palliative care (PC) access for historically minoritized patients with advanced breast cancer (ABC) persist. Insight into patient and clinician perspectives are needed to inform future models aimed at improving equity in PC access and outcomes. Objectives: To explore qualitative barriers and facilitators to early PC access in an urban setting with Black and Latina women with ABC. Methods: In this qualitative descriptive study, we conducted one-on-one interviews with Black and Latina women with ABC (N = 20) and interdisciplinary clinicians (N = 20) between February 2022 and February 2023. Participants were recruited from urban academic and community cancer clinics. Transcripts were analyzed using an inductive coding and thematic analysis approach. Results: Barriers identified by both patients and clinicians included lack of communication between oncology, PC, and primary care teams, limited understanding of PC among patients and non-PC clinicians, language and health literacy-related communication challenges, and racism and marginalization, including implicit bias and lack of diverse racial/ethnic representation in the supportive care workforce. Facilitators identified by both patients and clinicians included patient-to-patient referrals, support groups breaking cultural stigma on topics including self-advocacy and PC, referrals from trusted providers, and community organizations' abilities to overcome challenges related to social determinants of health, most specifically logistical and financial support. Conclusions: Patients and clinicians reported similar barriers and facilitators to PC access, most commonly through the lens of care coordination and communication. These findings will inform future adaptation of a culturally and linguistically care model to improve access to early PC services for Black and Latina women with ABC.